2019
DOI: 10.1186/s12934-018-1046-0
|View full text |Cite
|
Sign up to set email alerts
|

Sustainable biosurfactant produced by Serratia marcescens UCP 1549 and its suitability for agricultural and marine bioremediation applications

Abstract: BackgroundBiosurfactants are surface-active agents produced by microorganisms that have higher efficiency and stability, lower toxicity and higher biocompatibility and biodegradability than chemical surfactants. Despite its properties and potential application in a wide range of environmental and industrial processes, biosurfactants are still not cost-competitive when compared to their synthetic counterparts. Cost effective technologies and renewable raw substrates as agro-industrial and regional waste from no… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
49
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
2
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 105 publications
(55 citation statements)
references
References 69 publications
(107 reference statements)
4
49
0
2
Order By: Relevance
“…Preliminary biochemical characterization showed that the bioemulsifier had a polymeric structure, composed of lipids (37.6%), proteins (28.2%), and carbohydrates (14.7%). Similarly, Araújo et al [48] carried out these methodologies to obtaining the biochemical composition of biosurfactant produced by Serratia marcescens UCP 1549 and revealed the presence of 43% lipids, 32% proteins, and 11% carbohydrates, suggesting its polymeric nature. e biosurfactant obtained by Stenotrophomonas sp.…”
Section: Characterization Of Bioemulsifiermentioning
confidence: 99%
“…Preliminary biochemical characterization showed that the bioemulsifier had a polymeric structure, composed of lipids (37.6%), proteins (28.2%), and carbohydrates (14.7%). Similarly, Araújo et al [48] carried out these methodologies to obtaining the biochemical composition of biosurfactant produced by Serratia marcescens UCP 1549 and revealed the presence of 43% lipids, 32% proteins, and 11% carbohydrates, suggesting its polymeric nature. e biosurfactant obtained by Stenotrophomonas sp.…”
Section: Characterization Of Bioemulsifiermentioning
confidence: 99%
“…PG was first isolated in the 1920s, its structural features were identified in the 1930s, and structure elucidation was completed in the 1960s [ 163 , 164 , 165 , 166 ]. Serratia marcescens is the major source of PG production [ 59 , 60 , 61 , 62 , 81 , 82 , 83 , 84 , 85 , 86 , 87 , 88 , 89 , 90 , 91 , 92 , 93 , 94 , 95 , 96 , 97 , 98 , 99 , 100 , 101 , 102 , 103 , 104 , 105 , 106 , 107 , 108 , 109 , 110 , 111 , 112 , 113 , 114 , 115 , 116 , 117 , 118 , 119 , 120 , 121 , 122 , 123 , 124 , 125 , …”
Section: Introductionmentioning
confidence: 99%
“…Some PG-related reviews reported the production of PG from S. marcescens using commercial media such as nutrient broth, peptone glycerol broth, and seed oils as the C/N sources [ 156 , 161 , 162 , 166 , 168 , 171 ]. The biological potentials of PG especially in the field of anticancer have also been reviewed [ 156 , 157 , 158 , 159 , 160 , 161 , 162 , 166 , 168 , 169 , 171 ]. For example, a review of the characteristics and potential therapeutic anticancer-drug applications of PG from Serratia was introduced by Darshan and Manonmani [ 180 ], while the structure, chemical synthesis, and biosynthesis of PGs as natural products were summarized by Hu et al [ 157 ].…”
Section: Introductionmentioning
confidence: 99%
“…This is include P. aeruginosa [34, 35], Salmonella enteridis [36], Acinetobacter sp. [37], and Serratia Marcescens [38]. Gram positive bacteria are known as professional one in the production of BLM.…”
Section: Discussionmentioning
confidence: 99%